MALIGNANT MELANOMA – CUTANEOUS METASTASES - Padmavathy, L (Medknow Publications, 2008)
Melanoma composed of melanocytes may arise in the skin or other tissues harboring melanocytes, such muco-cutaneous junctions, mucosa including the conjunctiva, iris, choroids and substantia nigra.1 Metastases to the skin and subcutaneous tissues from a malignant melanoma are less common. A case of multiple painless nodules on the body that revealed metastatic deposits of melanoma on histopathological examination is being reported.